The Politics of Translation in International Relations
XII, 266 p. 1 illus.
Keywords: This volume concerns the role and nature of translation in global politics. Through the establishment of trade routes, the encounter with the ‘New World’, and the circulation of concepts and norms across global space, meaning making and social connections have unfolded through practices of translating. While translation is core to international relations it has been relatively neglected in the discipline of International Relations. The Politics of Translation in International Relations remedies this neglect to suggest an understanding of translation that transcends language to encompass a broad range of recurrent social and political practices. The volume provides a wide variety of case studies, including financial regulation, gender training programs, and grassroot movements. Contributors situate the politics of translation in the theoretical and methodological landscape of International Relations, encompassing feminist theory, de- and post-colonial theory, hermeneutics, post-structuralism, critical constructivism, semiotics, conceptual history, actor-network theory and translation studies. The Politics of Translation in International Relations furthers and intensifies a cross-disciplinary dialogue on how translation makes international relations. Zeynep Gulsah Capan is Lecturer at the University of Erfurt, Germany. Her research focuses on history and historiography, de- and postcolonial thought, and Eurocentrism. Filipe dos Reis is Assistant Professor in the Department of International Relations and International Organization, University of Groningen, Netherlands. His current research focuses on the history and politics of international law, imperial Germany, and maps. Maj Grasten is Assistant Professor at the Department of Management, Politics and Philosophy, Copenhagen Business School, Denmark. Her research sits at the intersection of Socio-Legal Studies and Global Governance, with particular focus on international organizations and legal bodies, experts and knowledge production in international law, and the legal foundations of markets.